MATHEMATICAL MODELS AND THERMODYNAMIC PROPERTIES OF MOISTURE SORPTION ISOTHERMS OF FERMENTED CASSAVA FLOUR BY RED YEAST RICE - Mutiara Nur Alfiah; Sri Hartini; Margareta Novian Cahyanti (UNIVERSITAS SEBELAS MARET (UNS), 2017)
This research aims to determine moisture sorption isotherm curves, moisture sorption isotherm models and thermodynamic properties of fermented cassava flour by red yeast rice. The moisture sorption isotherm model used are Guggenheim Anderson deBoer (GAB), Brunauer Emmet Teller (BET) and Caurie. Meanwhile, the test of modelling accuray by Mean Relative Deviation (MRD) and Root Mean Square Error (RMSE). The thermodynamic properties, i.e., enthalpy and entropy were calculated by Clausius - Clapeyron equation. The result shows that the moisture sorption isotherm curve on fermented cassava flour in a sigmoid form (type II). The GAB model is the best model for moisture sorption isotherm of fermented cassava flour by red yeast rice. The MRD and RMSE values at 30˚C, 35˚C and 40˚C are 3.12%, 2.71%, 3.81%, and 1.01, 0.35, 0.42, respectively. The monolayer moisture content at 30˚C, 35˚C and 40˚C are 6.61%, 6.27% and 6.91%, based on GAB model. Meanwhile, when the BET model was used, the monolayer moisture content are 4.92%, 4.86% and 5.19%, while by Caurie model are 6.37%, 6.18% and 5.30%, at 30˚C, 35˚C and 40˚C, respectively. The enthalpy and entropy of water sorption process were decreased when moisture content increased.